Mechanisms and treatment of atherosclerosis: focus on macrophages - Zhang, LingNa; Li, JiaWei; Kou, YuShun; Shen, LuFan; Wang, Hong; Wang, YiYuan; Ma, Ruiling; Wu, Tao; Yang, Xin; Gu, YuanHui; Yi, Lin (Frontiers in Immunology, 2024)
Macrophages are the basic mediators and coordinators of various types of chronic inflammation and play a crucial role in the formation and development of atherosclerosis(AS).In the complex microenvironment of atherosclerotic plaques, macrophages of different sources are exposed to different signal stimuli and thus polarized into various subpopulations.Various types of macrophages with predominantly M1 and M2 phenotypes also play different regulatory roles in the initiation and progression of AS. Lipid-lowering drugs, mainly statins, are widely used in clinical practice, but the adverse reactions are obvious and there is a lack of personalized treatment. Emerging targeted macrophage and Traditional Chinese medicine(TCM)-related therapies can regulate the cellular microenvironment, inhibit the polarization of M1 macrophages and promote the activation of M2 macrophages, providing new ideas for the prevention and treatment of AS.